Suara Rakyat Malaysia (SUARAM) as a Malaysian civil society organization: Strengths and challenges / Mohammed H. Y. Darkhalil - Mohammed H. Y., Darkhalil (2016)
Malaysian semi-democratic political system poses a question over the effectiveness of civil society organizations in Malaysia. Suara Rakyat Malaysia (SUARAM) is one of the most important secular human rights civil society organizations that aims to promote human rights in Malaysia, and its main target has been to reject detention without trial under the Internal Security Act. Experience of SUARAM can be considered a realistic example of Malaysian NGOs which partially oppose the policies of government. A case study on SUARAM can highlight the ability of Malaysian civil society to achieve their goals and highlights the main challenges to civil society activism in the country. This study argues that the role of Malaysian civil society is crucial but inefficient in promoting political rights. To put it briefly, findings of this study show that hegemony over Malaysian civil society by the state imposes a number of challenges that negatively influence the work of civil society groups. Despite the significant achievements of civil society groups such as SUARAM, those challenges have curbed democratization process in the country.